FAKTOR RISIKO KETUBAN PECAH DINI TERHADAP KEJADIAN ASFIKSIA BAYI BARU LAHIR DI RUMAH SAKIT UMUM DAERAH WONOSARI GUNUNG KIDUL YOGYAKARTA TAHUN 2009 - Susilo Rini; Ponisah Ponisah (Viva Medika, 2011)
Asphyxia can occur during pregnancy, birth process, or in the period immediately after a mother gave birth. Asphyxia has many risk factors such as maternal, plasenta, foenikulus andfetal factor. One of the risk factor that can be the cause of aaphyxia is premature ruptura ofmembranes. In Wonosari Gunungkidul, there are 210 cases of asphyxia in 2009 which meansthat 5,52 % of the 69 babies died because of asphyxia. The number raises from only 5% in2008. The Aims of this research is To know how much the risk factor of premature ruptura ofmembranes on mother who gave birth to the asphyxia incedence of newborn babies in RSUDWonosari Gunungkidul in the year of 2009. This study used case control method. The sample of this research is newborn baby asphyxiaand non asphyxia of the mother who gave birth whether they are KPD or non KPD in RSUDWonosari in 2009. The number of the sample is 140 babies which are divided into theexperimental (case) group which consists of 70 babies, and the control group which consistsof 70 babies . The researcher used purposive sampling to select the sample. This study usedchi-square to analize the data. To measure the KPD risk in relation to asphyxia, the researherused OR standard/value with 95% of confidence interval and 5% degree of error. The Result is Asphyxia incidence of newborn babies from mothers who got KPD is 62,7%.There is a significant relationship between asphyxia incedence of newborn babies with therisk of KPD by the value chi-square is 10,367 with 95% confidence interval and 5% degreeof error and p value <0.05 was 0.001. KPD is a risk factor of asphyxia incidence of newbornbabies with value of Odds Ratio is 3,065. The conclusion: A mother who gave birth with premature ruptur of membranes has a risk of3,065 times more to the aspyxia incedence of newborn babies. Keyword: Asphyxia incedence of newborn babies, premature rupture of membranes, oddsratio.